CITED2 modulation of trophoblast cell differentiation: insights from global transcriptome analysis. Issue 5 (May 2016) - Imakawa, Kazuhiko; Dhakal, Pramod; Kubota, Kaiyu; Kusama, Kazuya; Chakraborty, Damayanti; Karim Rumi, M A; J Soares, Michael
Abstract : Trophoblast stem (TS) cells possess the capacity to differentiate along a multi-lineage pathway yielding several specialized cell types. The regulatory network controlling trophoblast cell differentiation is poorly understood. Cbp/p300-interacting transactivator with Glu/Asp-rich carboxy-terminal domain, 2 (CITED2) has been implicated in the regulation of placentation; however, we know little about how CITED2 acts to influence trophoblast cells. Rat Rcho-1 TS cells can be manipulated to proliferate or differentiate into specialized trophoblast lineages and are an excellent model for investigating trophoblast differentiation. CITED2 transcript and protein showed a robust induction during Rcho-1 TS cell differentiation. We used an shRNA knockdown approach to disrupt CITED2 expression in order to investigate its involvement in trophoblast cell differentiation. RNA-sequencing was used to examine the impact of CITED2 on trophoblast cell differentiation. CITED2 disruption affected the differentiating trophoblast cell transcriptome. CITED2 possessed a prominent role in the regulation of cell differentiation with links to several signal transduction pathways and to hypoxia-regulated and coagulation processes. In summary, our findings indicate that CITED2 contributes to the regulation of trophoblast cell differentiation. Reproduction (2016) 151 1–8